The Pope's exorcist [videorecording (Blu-Ray)] - Petroni, Michael; Spiliotopoulos, Evan; McCreary, R. Dean; Hastings, Chester (Screenwriter); Katz, Jeff, 1978-; Kurzel, Jed; Crowe, Russell, 1964-; Zovatto, Daniel, 1991-; Essoe, Alex; Marsden, Laurel; Nero, Franco; Amorth, Gabriele; et al. (Sony Pictures Home Entertainment, 2023)
The Chief Exorcist of the Vatican, Father Amorth investigates a young boy's terrifying possession and ends up uncovering a centuries-old conspiracy the Vatican has desperately tried to keep hidden.